Influence Mechanism of Dynamic Evolution of Chinese Entrepreneurs’ Entrepreneurial Motivation on Performance—The Role of Turning Points and Empathy - Zhao, Yiqi; Zhao, Xianfeng; Qin, Yuanjian (Frontiers in Psychology, 2020)
Tnriched and expanded the research results in the field of entrepreneurial motivation of Chinese entrepreneurs.From the perspective of entrepreneurial motivation, this study analyzes the dynamic evolution process of entrepreneurial motivation of Chinese entrepreneurs, extracts the entrepreneurial process rules of dynamic evolution of Chinese entrepreneurs, and provides a new path for enriching and expanding the research on entrepreneurial motivation of Chinese entrepreneurs.-interest motivation, other-orientation motivation, TP/MTP, empathy, delayed gratification, entrepreneurial failure and entrepreneurial performance. Through the analysis of the internal relationship between these factors, the paper extracts the entrepreneurial process rules of dynamic evolution of Chinese entrepreneurs’ motivation, and reveals the mechanism of dynamic evolution of entrepreneurial motivation. The theoretical contributions of this paper are mainly reflected in the following two aspects: The theoretical contributions of this paper are mainly reflected in the following two aspects:(1) Enriched and expanded the research results in the field of entrepreneurial motivation of Chinese entrepreneurs.From the perspective of entrepreneurial motivation, this study analyzes the dynamic evolution process of entrepreneurial motivation of Chinese entrepreneurs, extracts the entrepreneurial process rules of dynamic evolution of Chinese entrepreneurs, and provides a new path for enriching and expanding the research on entrepreneurial motivation of Chinese entrepreneurs. (2) It enriches and complements the study on the triggering events (TP) of the dynamic evolution of entrepreneurial motivation. Using grounded theory, this paper deeply analyzes the reasons for the dynamic evolution of entrepreneurial motivation, and provides empirical evidence for the research on the evolution of localized entrepreneurial motivation in China.